Zur Glazialmorphologie und präkeramischen Archäologie des mexikanischen Hochlandes während des Spätglazials (Wisconsin) und Holozäns - Heine, Klaus (ERDKUNDE, 1973)
Four glacier advances can be identified on the 4461 metre high Malinche volcano, recognisable through moraines, glacier abrasions, periglacial deposits (sands, periglacial deposits, varves) and cryoturbations. The sediments of the individual glacier advances are separated from each other by volcanic brecchias, ash and pumice deposits, fluviatile debris, aeolian loess-like deposits, mud flows and various fossil soils. The stratigraphie arrangement of the glacial and periglacial sediments has been based on tephrochronological and paleopedological observations. A number of 14C-age determinations on fossil soils and charcoal supplement the fieldwork. In the Sierra Nevada (Popocatepetl, 5452 metres and Iz taccihuatl, 5286 metres) the traces of a further fifth glacial advance in additional to the four glaciations already mentioned can be found. The glacial traces of the Sierra Nevada can be shown to be parallel to those of the Malinche; in this way the individual glacier advances can be more accurately dated. The fourth glacier advance emerges as having occurred at around 2,000 years B.P., the fifth at around the beginning of the 19th century. Up to four retreat moraines show evidence of the stage-wise back-melting of the glacier since about 1890. The research results allow relatively exact dating of the glaciations. It can be shown that the dating efforts for the moraines of Iztaccihuatl, put forward by de Terra et. al. (1949) and White (1962a + b) require revision. A paleoclimatic interpretation of the morphological in dices yields new insights into the climatic development of the last 40,000 years B.P. for Mexico. The extra-tropical periods of maximum glaciation (high glacial) correspond in Mexico to periods of time with a cold and dry climate without significant glacier formation. Apart from the oldest glacier advance, it is not until the later Wisconsin Ice Age that a number of glacier advances occur on the Mexican volcanoes, caused by increased precipitation and having only a short duration. Comparison of the recent pleistocene and holocene glacial deposits and fossil soils of Mexico with the quaternary stratigraphy of the north American Rocky Mountains shows amazingly good agreement. The glacial advances of Mexico are temporally somewhat later in the last period of the Pleistocene than those of the Rocky Mountains, which confirms assumptions about the general circulation of the atmosphere during the period. On the basis of these research results, the age the Tepex pan man and the Hueyatlaco (State of Puebla) archaeo logical site are discussed.